Modes of Discourse: A Cross-Cultural Study of Essays Written in English and Spanish by EFL Students in Costa Rica (Part 1) - Saborío Pérez, Ileana (2007)
Mediante un análisis contrastivo se evalúan los patrones retóricos interculturales desarrollados por estudiantes nativohablantes del español, en el proceso de escritura. Se plantean cinco preguntas de investigación con respecto a las diferencias o similitudes cuando se escribe en español o en inglés, y su influencia en la escritura para el desarrollo del estilo y la estructura oracional, así como sus implicaciones pedagógicas.A contrastive analysis was used to evaluate the cross-cultural rhetorical patterns developed by native Spanish-speaking students, in the writing process. Five research questions were posed with respect to similarities or differences when writing in Spanish or English, and their influence on writing in the development of style and sentence structure, as well as their pedagogical implications.